Train-the-Trainers: Implementing Outcomes-based Teaching and Learning in Malaysian Higher Education (Malaysian Journal of Learning and Instruction, 2011)
The decision by the Minister of Higher Education, that Malaysian post-secondary institutions should move to outcomes-based teaching and learning (OBTL), involves a change in teaching in over 1,000 institutions. This massive changeover would be accomplished using the â€œTrain-the-Trainersâ€ model in a series of workshops. We are proud to play a role in the first of these Train-the-Trainers programmes. In this article we explain how OBTL was conceptualised in the constructive alignment model, and how this first programme was structured. The major outcome was that each trainer would devise their own training programme to suit the conditions of their institution. The results were impressive but there were some difficulties; mainly to do with limiting the number of intended learning outcomes to a workable number, that would need to be addressed in order to achieve optimal outcomes.